Disentangling Benefit-Sharing Complexities of Oil Extraction on the North Slope of Alaska - Maria S. Tysiachniouk (Sustainability, 2020)
This paper analyses benefit-sharing arrangements between oil companies, native corporations, the North Slope Borough, and Indigenous Peoples in Alaska. It aims to disentangle the complexities of benefit-sharing to understand existing procedural and distributive equity. We identified benefit-sharing regimes involving modes, principles, and mechanisms of benefit-sharing. This includes modes that reflect institutionalized interactions, such as paternalism, company centered social responsibility (CCSR), partnership, and shareholders. Principles can be based on compensation, investment and charity. Mechanisms can involve negotiated benefits and structured benefits, mandated by legislation, contracts, or regulation. Furthermore, mechanisms can involve semi-formal and trickle-down benefits. Trickle-down benefits come automatically to the community along with development. The distribution of money by the North Slope Borough represents the paternalistic mode, yet involves investment and mandated principles with top–down decision making. They are relatively high in distributional equity and low in participatory equity. Native corporations predominantly practice the shareholders’ mode, investment principle, and mandated mechanisms. The oil companies’ benefit-sharing represents a mixed type combining CCSR and partnership modess, several principles (investment, compensatory, charity) and multiple types of mechanisms, such as mandated, negotiated, semi-formal and trickle-down. These arrangements vary in terms of distributive equity, and participatory equity is limited.